Knowledge, attitude, and practices in research among postgraduate students in dental institutions in Bengaluru City, India - Nitya Sharma; M Pramila; Archana Krishnamurthy; G K Umashankar; Ranganath; Nikhil Ahuja (Wolters Kluwer Medknow Publications, 2014)
Introduction: Research is not a separate specialty which is practiced by a few, but it is a systematic approach of reasoning, documenting, analyzing, and reporting unusual clinical observations that we come across in everyday clinical practice. This study was conducted to assess research-related knowledge, attitude, and practices among postgraduate students in dental institutions in Bangalore city. Materials and Methods: A cross-sectional survey was conducted using a structured and validated questionnaire. A sample size of 210 postgraduate students was determined. Study was conducted among 2 nd and 3 rd year postgraduate students in 4 randomly selected dental institutions. Descriptive statistics, Chi-square test, and Student's t-test were used to analyze the data. Results: The average percentage of correct responses was 56.7% and 52.6% in 3 rd year and 2 nd year postgraduate students, respectively. Overall, positive attitude was seen in both the groups and was significantly more in 3 rd years in relation to improvement of patient outcome with research and importance of research training during the post graduate course. Research in practice was carried out by 56.9% and 36% of 3 rd and 2 nd year postgraduate students, respectively. The most common obstacle stated for research was the lack of adequate financial and technical facilities for research. Conclusion: The study revealed fair knowledge and a positive attitude toward research but postgraduates failed to transform it into actual practice.